L’espace public contestataire à l’épreuve de la délibération en Algérie - Nabila Aldjia Bouchaala; Aïssa Merah (Communication)
The authors analyze the slogans of the February 22 protest movement in Algeria. They hypothesize that these acts of language show that the emotional protest was driven by a rational decision, which helped rally others to the cause. The corpus is made up of slogans from the six months of popular protest, which the authors use to track the evolution of the demands made during the “Hirak” movement.